The effect of scanning technology and UPC placement on supermarket self‐checkout. Issue 2 (3rd November 2017) - Mumani, Ahmad; Stone, Richard; Wang, Zhonglun
Abstract : Self‐checking services are offered in many supermarkets. In order to checkout efficiently, customers must locate and scan the Universal Product Code (UPC) of the items with relative ease. Otherwise, their preferences toward using the self‐checkout (SCO) stations may be negatively affected. The current literature has no focus on UPC location, and the scanning technology used effect on performance and preferences. The purpose of this study is to investigate the effect of these from an operational and ergonomic perspective. To that end, 2 UPC placement techniques (current and recommended placement) and 2 scanning technologies (bi‐optic and handheld scanners) were tested. The total scanning time, individual items scanning time, trunk posture, total number of wrong twists/flips, individual items wrong flips, muscle activities, and participants' subjective preferences were measured. The results revealed that total scanning time was significantly reduced when using bi‐optic scanner ( F  = 20.9, P  < 0.01). The recommended UPC placement led to a significant improvement on UPC anticipation for both scanning technologies ( F  = 16.8, P  < 0.01). Additionally, exposure to non‐neutral trunk posture(s) was shown to be significantly decreased in the bi‐optic condition ( F  = 10.4, P  < 0.01). Proper UPCs' placement and bi‐optic scanner can positively improve the efficiency and experience of the SCO. Abstract : The results revealed that total scanning time was significantly reduced when using bi‐optic scanner ( F = 20.9, P < .01). The recommended Universal Product Code (UPC) placement led to a significant improvement on UPC anticipation for both scanning technologies ( F = 16.8, P < .01). Additionally, exposure to non‐neutral trunk posture(s) was shown to be significantly decreased in the bi‐optic condition ( F = 10.4, P < .01). Proper UPCs' placement and bi‐optic scanner can positively improve the efficiency and experience of the self‐checkout.